2004
DOI: 10.1177/171516350413701007
|View full text |Cite
|
Sign up to set email alerts
|

Retaining Pharmacists in Rural Canada

Abstract: Background: The Multistakeholder Framework of Rurality project was funded by Health Canada's Rural and Remote Health Innovations Initiative. The aim of this project was to develop a tool to assist rural communities with health human resource planning and to help governments and communities in recruiting and retaining health care providers in rural and remote communities. Methods: A national survey was sent to nurses, physicians, and pharmacists living in rural or remote communities to determine, among other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…While the limitations of Maslow’s hierarchy of needs model were acknowledged, it was argued that such a framework is still useful for understanding physicians’ motivations [46]. The choice to remain in rural practice for an extended period of time was generally found to be made by those health professionals who were in their middle years, partnered, and/or raising a family, especially if the children were preschool or primary school aged [27,45,57,61]. Cosgrave et al argued that life stage, rather than rural origin, was the major determinant of turnover for both locals and non-locals, and that those in early adulthood (usually in their early-to-mid 20s) were the most likely to leave within a couple of years of working, regardless of background [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the limitations of Maslow’s hierarchy of needs model were acknowledged, it was argued that such a framework is still useful for understanding physicians’ motivations [46]. The choice to remain in rural practice for an extended period of time was generally found to be made by those health professionals who were in their middle years, partnered, and/or raising a family, especially if the children were preschool or primary school aged [27,45,57,61]. Cosgrave et al argued that life stage, rather than rural origin, was the major determinant of turnover for both locals and non-locals, and that those in early adulthood (usually in their early-to-mid 20s) were the most likely to leave within a couple of years of working, regardless of background [27].…”
Section: Resultsmentioning
confidence: 99%
“…However, many retention research studies to date lacked analytical depth; only two published studies [27,46] proposed a conceptual framework that moved beyond a simple push and pull understanding. Furthermore, much of the existing research focused on doctors [46,52,57,60], dentists [44,48], or pharmacists [55,61]. These are generally considered high-status health professions [62].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a USA study on the influence of practice location choices of rural-based primary care physicians over their life course found that living a happy and satisfying life was an important factor for retention [47]. Other rural retention studies have also identified life stage as being an important influence on the decision to stay [9,13,[58][59][60][61].…”
Section: Placementioning
confidence: 99%
“…The numbers of pharmacists per 100,000 population in the Northwest Territories (46), BC Northeast (55), Yukon (66) and BC Northwest (68) are relatively low and are roughly comparable to those found in Australia in 1999 (32 in remote areas and 60 in small rural areas), at the time that nationally funded rural pharmacy programs began to be initiated (26). Community attributes that enhance pharmacists' personal satisfaction and quality of life can contribute to both the selection of a pharmacy practice site and staying in the community long-term (19,20,36). Such professional and community-based characteristics to enhance the appeal of rural pharmacy practice have the potential to be addressed through innovative university and community interactions.…”
Section: Discussionmentioning
confidence: 85%
“…University-pharmacy collaborative rural models Extensive research has been conducted on factors related to recruitment and retention of rural pharmacists in Canada (19,20), the United States (21,22), New Zealand (23) and Australia (24), and the lack of consensus on ways of addressing these issues highlights the complexity of the problem. In Australia, recognition of the need to systematically provide infrastructure support for rural pharmacists has led to a nationally funded model known as the Rural and Remote Pharmacy Workforce Development Program that utilizes educational, professional, economic and research strategies and that has received international recognition (25).…”
Section: Rural Pharmacy In Canadamentioning
confidence: 99%